(untitled) (Zoological Records and Reviews, 2022)
Freshwater crabs (Crustacea: Brachyura) constitute one of the most diverse and ecologically important invertebrate groups in South Asian river systems, yet their taxonomy in peninsular India remains poorly resolved, with numerous nominal species inadequately described and several cryptic lineages awaiting formal recognition. This study presents a comparative taxonomic assessment of freshwater crabs across peninsular India, based on morphometric analysis of 1,847 specimens from 84 collection localities spanning the Eastern Ghats, Western Ghats, and Deccan Plateau, supplemented by molecular phylogenetic analysis of mitochondrial COI and 16S rRNA sequences from 312 individuals representing 58 putative species. Our analyses recover seven family-level lineages represented in peninsular India, with Gecarcinucidae constituting the dominant family (32 species, 14 genera). Integrative analysis identifies 8 candidate new species and resolves long-standing nomenclatural confusion in the genera Globitelphusa, Ghatiana, and Gubernatoriana. Mean COI divergence between morphologically similar but molecularly distinct lineages averages 9.4%, substantially exceeding the barcoding gap threshold and confirming the widespread occurrence of cryptic species in this group. An updated dichotomous key to the freshwater crab genera of peninsular India is provided. Forty-one percent of assessed species qualify as Threatened under IUCN criteria, with habitat specificity and small range size as primary vulnerability factors.